Age-Related Dynamics of Anti-Müllerian Hormone and its Correlation with Antral Follicle Count in Growing Heifers - Sharma, Prachi; K Hadiya, Kamlesh; S Layek, Siddhartha; G Koringa, Prakash; P Patil, Sanket; B Raval, Kathan; N Saripadiya, Bhautik (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The profitability of the dairy industry relies heavily on reproductive efficiency and genetic improvement, particularly in countries where dairy farming is vital for the economy. This study aimed to evaluate the relationship between Anti-Müllerian hormone (AMH) levels and antral follicle count (AFC) in female calves as potential biomarkers for predicting reproductive success in advanced breeding programs. A total of 31 female calves of indigenous and crossbred cattle breeds, aged six months, were selected and monitored over one year, with blood samples collected at 6, 12, and 18 months to assess AMH levels. Upon reaching 18 months, ultrasound examinations were performed to determine AFC. Based on the median follicle count of 34.40, irrespective of genetic makeup, the animals were divided into High AFC (n=15, 50.37±3.08) and Low AFC (n=16, 27.25±1.52) groups. Results indicated a significant decline in AMH levels over age. Mean AMH level decreased from 2.53±0.29 ng/mL at 6 months to 1.79±0.14 ng/mL at 18 months (p<0.05). Notably, higher AMH concentrations were consistently associated with greater AFC throughout the age groups (p<0.05), highlighting AMH’s potential as an early predictor of reproductive performance. The findings underscore the importance of AMH as a valuable biomarker in selecting heifers for in vitro embryo production programs at an early age, ultimately enhancing the efficiency of breeding strategies in the dairy industry.